Diskusi Mengenai Indeks Pembangunan Manusia dan Indeks Pembangunan Pemuda Dalam Rangka Peningkatan Daya Saing Pemuda Punguan Raja Panjaitan Dohot Boruna (PRPB) Kota Medan - Nancy Nopeline; Rimbun C.D Sidabutar; Herti Diana Hutapea (LPPM Universitas HKBP Nommensen, 2021)
The purpose of this community service is to provide insight and also to motivate young men by king panjaitan dohot boruna (PRPB) of the terrain city on which one of the topics was published on the human development index (ipm). The work is conducted on Friday, April 30, 2021, according to strict health protocols in the secretariat PRPB of the terrain of 29 people. The performance included opening, MC inviting participants to sing, ice breaking, socialization, video shows, the interview and feedback sessions. Building young people is not only about building young individuals but also about building a neighborhood that makes them a livelihood. Thus, youth development must be a cross section that touches on educational, health, welfare, employment, participation, politics, and gender equality. This exercise of devotion to the community is aimed at providing insight into the importance of the ipm problem especially in the square city, by engaging in discussion/socialization activities with young men by king panjaitan dohot boruna (PRPB) of terrain (PRPB). It also collaborates with professors at the economics and business faculty of the university of HKBP nommensen. This activity will be conducted to support sustainable entrepreneurial workshops that will be carried out by the terrain city PRPB for young people. The result of the activities summarizes the opinions of professors, youth, and PRPB administrators of the city of medan. The terrain city reached its highest ipm in northern Sumatra by 80.65 with the calculation of three aspects of knowledge, a standard of living, anda length of life anda healthy life.